Demystifying death: a qualitative study using the behavior change wheel framework to explore the palliative care education experiences of doctors, nurses, and community residents - Guodong Yang; Renxiu Wang; Jun Zhao; Kaiwen Ding; Longhui Xu; Yue Liu; Xiaoxuan Han; Chao Zhang; Cuiping Xu (Frontiers in Public Health)
ObjectiveTo explore the palliative care education experiences of doctors, nurses, and community residents.MethodsA semi-structured interview was conducted with 2 doctors, 8 nurses and 9 community residents in Jinan. Content analysis and behavior change wheel theory were used to analyze the interview content.ResultsMotivation: The road to be taken; Emotional touch of personal experiences; Prepare early; Not now. Capability: Multiple cognition; Need for a topic catalyst; Trust bias; Disconnect between learning and application; Treading on thin ice. Opportunity: Willing but unable; The Need for a larger voice and greater participation.ConclusionCommunity palliative care education requires greater attention. Community residents exhibit diverse perceptions and attitudes toward palliative care, reflecting the influence of personal experiences and sociocultural factors. Innovating the content and format of educational resources and enhancing education for community residents and medical staff will facilitate palliative care.